6th AIAA Atmospheric and Space Environments Conference 2014
DOI: 10.2514/6.2014-2752
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of fluid flow and collection efficiency for an SEA multi-element probe

Abstract: Numerical simulations of fluid flow and collection efficiency for a Science Engineering Associates (SEA) multi-element probe are presented. Simulation of the flow field was produced using the Glenn-HT Navier-Stokes solver. Three-dimensional unsteady results were produced and then time averaged for the heat transfer and collection efficiency results. Three grid densities were investigated to enable an assessment of grid dependence. Simulations were completed for free stream velocities ranging from 85-135 m/s, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…However, the model over predicts the power by approximately 5.5% at = 135 m/s and = 93.1 kPa. Figure 5 also shows results using heat transfer correlations generated from CFD results 6 . These correlations were generated by maintaining the wire at a constant temperature in the CFD model and calculating the resulting heat transfer.…”
Section: B Dry Conditionsmentioning
confidence: 98%
See 4 more Smart Citations
“…However, the model over predicts the power by approximately 5.5% at = 135 m/s and = 93.1 kPa. Figure 5 also shows results using heat transfer correlations generated from CFD results 6 . These correlations were generated by maintaining the wire at a constant temperature in the CFD model and calculating the resulting heat transfer.…”
Section: B Dry Conditionsmentioning
confidence: 98%
“…Overall, the radiation term was found to be very small in the calculations so the sensitivities of the parameters were not examined in detail. A recent CFD study 6 of the SEA multi-wire probe indicated that the mass flow through the shroud is about 80% of the upstream value based on the projected cross-sectional area of the probe. For calculating the heat-transfer coefficient of the elements, the far field conditions based on the corrected mass flow in the inlet were deemed the most appropriate.…”
Section: Property Valuesmentioning
confidence: 98%
See 3 more Smart Citations